1994
DOI: 10.1017/s0305004100072030
|View full text |Cite
|
Sign up to set email alerts
|

Odd perfect numbers

Abstract: It is not known whether or not odd perfect numbers can exist. However it is known that there is no such number below 10300 (see Brent[1]). Moreover it has been proved by Hagis[4]and Chein[2] independently that an odd perfect number must have at least 8 prime factors. In fact results of this latter type can in priniciple be obtained solely by calculation, in view of the result of Pomerance[6] who showed that if N is an odd perfect number with at most k prime factors, thenPomerance's work was preceded by a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Moreover, Hagis [5] has shown (his announcement of this result [6] came a few years earlier in 1975) that an odd perfect number must have at least 8 prime factors. Furthermore, Heath-Brown [7] has shown that if n is an odd perfect number with at most k prime factors, then n < 4'\…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Hagis [5] has shown (his announcement of this result [6] came a few years earlier in 1975) that an odd perfect number must have at least 8 prime factors. Furthermore, Heath-Brown [7] has shown that if n is an odd perfect number with at most k prime factors, then n < 4'\…”
Section: Resultsmentioning
confidence: 99%
“…> prevprime(\OO); 97 We can let Maple list for us the first 50 prime numbers: > s:=NULL: for i to 50 do s:=s,ithprime(i)od:s; 2, 3,5,7,11,13,17,19,23,29,31,37,41,43,47,53,59,61,67,71,73,79,83,89,97,101,103,107,109,113,127,131,137,139,149,151,157,163,167,173,179,181,191,193,197,199,211,223,227,229 Generating Bernoulli numbers:…”
mentioning
confidence: 99%
“…Pomerance [26] gave an effective bound in terms of k. This was improved in succession by Heath-Brown [13], Cook [5], and finally by the second author to N < 2…”
Section: Question 2 Are There Any Odd Perfect Numbers?mentioning
confidence: 93%
“…In 1977, Pomerance [8] gave an explicit upper bound in terms of k. Heath-Brown [5] improved the bound to N < 4 4 k , and Cook [2] reduced this bound to N < D 4 k with D = (195) 1/7 . Nielsen [6] slightly improved and generalised Cook's method; he proved that if N is an odd multiperfect number with k distinct prime factors, then N < 2 4 k .…”
Section: Introductionmentioning
confidence: 99%